Benefits and Challenges of Applying Bacteriophage Biocontrol in the Consumer Water Cycle - Brandon Reyneke; Benjamin Havenga; Monique Waso-Reyneke; Sehaam Khan; Wesaal Khan (Microorganisms, 2024)
Bacteria (including disinfection- and antibiotic-resistant bacteria) are abundant in the consumer water cycle, where they may cause disease, and lead to biofouling and infrastructure damage in distributions systems, subsequently resulting in significant economic losses. Bacteriophages and their associated enzymes may then offer a biological control solution for application within the water sector. Lytic bacteriophages are of particular interest as biocontrol agents as their narrow host range can be exploited for the targeted removal of specific bacteria in a designated environment. Bacteriophages can also be used to improve processes such as wastewater treatment, while bacteriophage-derived enzymes can be applied to combat biofouling based on their effectiveness against preformed biofilms. However, the host range, environmental stability, bacteriophage resistance and biosafety risks are some of the factors that need to be considered prior to the large-scale application of these bacterial viruses. Characteristics of bacteriophages that highlight their potential as biocontrol agents are thus outlined in this review, as well as the potential application of bacteriophage biocontrol throughout the consumer water cycle. Additionally, the limitations of bacteriophage biocontrol and corresponding mitigation strategies are outlined, including the use of engineered bacteriophages for improved host ranges, environmental stability and the antimicrobial re-sensitisation of bacteria. Finally, the potential public and environmental risks associated with large-scale bacteriophage biocontrol application are considered, and alternative applications of bacteriophages to enhance the functioning of the consumer water cycle, including their use as water quality or treatment indicators and microbial source tracking markers, are discussed.